Improving the students’ writing skill using weblog - Novarita novarita; Vennycintia Maharani (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2021)
This study used weblog to improve the students’ writing skill and took the second-grade students at junior high school Sentosa Bhakti Baturaja. Then, to take the data, the reserchers used the pre-experimental design. The objective was to find out whether there was any significantly effective to improve students in writing skill by the use weblog to the eighth-grade student of SMP Sentosa Bhakti Baturaja. This study took VIII.B that consisted of 18 students as the sample by applying cluster random sampling. The data was collected by using test. The test was in from of writing test. The data obtained through test and analysis was done by using statistical analysis (paired sample t-test). The result it was found the mean score of pretests was 50 and the mean score of posttests was 73,55. Based on the data analysis the researcher concluded there was significantly effective to use weblog to improve students writing skill descriptive text at SMP Sentosa Bhakti Baturaja before and after treatment. Since, the sig. (2-tailed) =0.000 less than significant level (?=0.05), the writers concludes that the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. It means that there is significant effect in using a weblog to improve students writing skill at SMP Sentosa Bhakti Baturaja. Keywords: writing skill; weblog; descriptive text